2007
DOI: 10.1038/nature06233
|View full text |Cite
|
Sign up to set email alerts
|

The origin of spontaneous activity in the developing auditory system

Abstract: Spontaneous activity in the developing auditory system is required for neuronal survival as well as the refinement and maintenance of tonotopic maps in the brain. However, the mechanisms responsible for initiating auditory nerve firing in the absence of sound have not been determined. Here we show that supporting cells in the developing rat cochlea spontaneously release ATP, which causes nearby inner hair cells to depolarize and release glutamate, triggering discrete bursts of action potentials in primary audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

36
675
4
3

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 499 publications
(718 citation statements)
references
References 43 publications
36
675
4
3
Order By: Relevance
“…Study of the neonatal rat organ of Corti has also revealed spontaneous pulsatile ATP release from the columnar epithelial cells of the transient Kölliker's organ (greater epithelial ridge), located medial to the inner hair cells [2]. The release mechanism is likely to engage the same extracellular ATP-mediated ATP release process and has Fig.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Study of the neonatal rat organ of Corti has also revealed spontaneous pulsatile ATP release from the columnar epithelial cells of the transient Kölliker's organ (greater epithelial ridge), located medial to the inner hair cells [2]. The release mechanism is likely to engage the same extracellular ATP-mediated ATP release process and has Fig.…”
Section: Discussionmentioning
confidence: 97%
“…b P2Y 4 immunolabeling was only present on the sensory epithelium and greater epithelial ridge (arrowheads). c P2Y 6 [2] differentiates into the inner sulcus region. P2Y 4 expression is pronounced here (Figs.…”
Section: P2y Receptor Expression Around the Onset Of Hearing (P6-p12)mentioning
confidence: 99%
See 2 more Smart Citations
“…Purinergic signalling appears to be involved in the regulation of hearing sensitivity under stress conditions, acting via the P2X 2 subtype of the receptor in tissues lining the endolymphatic compartment [2,5]. There is increasing evidence that ATP is a neuromodulator at the primary synapse between the inner hair cell and auditory afferent neurones [6] and is a neurotransmitter at the type II synapse with the outer hair cells [7] which regulates the generation of spontaneous neural activity in the developing cochlea [8]. ATP acts as a vasoactive signal, regulating cochlear blood flow [9], and appears to be involved in regulating cochlear mechanics via an action on the Deiters' supporting cells of the auditory sensory organ [10][11][12].…”
Section: Introductionmentioning
confidence: 99%